2015
DOI: 10.20533/ijehis.2046.3332.2015.0007
|View full text |Cite
|
Sign up to set email alerts
|

Moving towards Preceptorship Model and Blended Learning Methodologies in Baccalaureate Nursing Education in Pakistan

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…Furthermore, the preceptors assisted the student to identify individual learning needs and identified learning opportunities for them. This finding concurs with other researchers' reports that the presence of clinical preceptors is important for students' learning as the preceptors provide continuous support [17], [24] close guidance and assistance [25] as well as a one-on-one learning opportunity [1]. Similarly, the key determinants for student satisfaction of their clinical learning experience have been reported as quality clinical facilitator support and the availability of a range of clinical learning opportunities [26].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the preceptors assisted the student to identify individual learning needs and identified learning opportunities for them. This finding concurs with other researchers' reports that the presence of clinical preceptors is important for students' learning as the preceptors provide continuous support [17], [24] close guidance and assistance [25] as well as a one-on-one learning opportunity [1]. Similarly, the key determinants for student satisfaction of their clinical learning experience have been reported as quality clinical facilitator support and the availability of a range of clinical learning opportunities [26].…”
Section: Discussionsupporting
confidence: 89%
“…Dias et al. [24] considers communication as the backbone of the preceptorship model. According to them communication channels should be kept open with training institutions, preceptors and students to ensure effective clinical teaching and learning.…”
Section: Discussionmentioning
confidence: 99%
“…That is why the teaching style, knowledge and experience of the preceptor are important to the preceptorship programme. A qualitative study by Dias et al ( 2015 :53) conducted in Pakistan, interviewing nine students and six preceptors in focus group discussions found that students reported that preceptors are an invaluable resource. Miller, Vivona and Roth ( 2016 :2020) found in their study that a majority of respondents reported positive experiences with their preceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a study in the US with 34 preceptors and 30 novice nurses as participants, Hickerson, Terhaar and Taylor ( 2016 :61) found that the preceptor support programme was associated with positive assessments by the novice nurses of their preceptors’ teaching and support. It can be seen that students appreciate the preceptorship model as an innovative way of teaching pedagogy (Dias et al 2015 :53). In a study conducted in Ethiopia with 109 respondents, Teferra and Mengistu ( 2017 :86) found that of the respondents who are familiar with the clinical preceptorship concept, 96.3% of the respondents were classified as having a favourable attitude towards clinical preceptorship.…”
Section: Introductionmentioning
confidence: 99%